How to teach English. - Harmer, Jeremy, 1947?- (Harlow : Pearson Education, 2009)
How to Teach English is an easy-to-read, practical introduction to English Language Teaching. It is an essential reference work for trainee teachers preparing for exams. New to 2nd Edition: * New glossary to explain teaching terms * DVD with classroom demonstrations of core classroom techniques * New chapter on testing
Keywords: Engels -- Didactiek